2017
DOI: 10.5812/mejrh.12354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge, Attitude and Practice of Personnel in Operating Room, ERCP, and ESWL Towards Radiation Hazards and Protection

Abstract: Background: Recently, X-rays radiation hazards rise with the exposure of patients and personnel. Exposure of people to radiation in the operating rooms is an important problem to study the safety of personnel and patients. To date, few studies are accomplished to evaluate knowledge, attitude, and practice (KAP) among personnel in hospitals. The current study aimed at evaluating KAP level of radiation hazards and protection amongst personnel in the operating room. Methods: A questionnaire-based, cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Also, reliability was evaluated by test-retest method that the Pearson's correlation coefficient was 0.81. This instrument was appropriate for radiology ward but was not sufficient and relevant to measure radiation protection in the operating room field [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, reliability was evaluated by test-retest method that the Pearson's correlation coefficient was 0.81. This instrument was appropriate for radiology ward but was not sufficient and relevant to measure radiation protection in the operating room field [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In stage one, the items were extracted through literature review, including the national and international guidelines [7,8,26], books [27,28] and related articles within the past 10 years [1,[9][10][11][12][13][17][18][19][20][21][22][23][24][25]. Then the selected items were evaluated by the panel of experts.…”
Section: Design Setting and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open Access: e-Journal among healthcare workers has been studied in several countries in term of knowledge, attitude and practice. There is study which concluded that the level of KAP regarding radiation protection among healthcare worker was inadequate (Moshfegh et al, 2017). Simultaneously, a study by Sharma et al, (2016) concluded that there is 'knowledge-practice gap' on the use of personal protective devices among radiographers.…”
Section: Ijphcsmentioning
confidence: 99%
“…Occupational exposure of individuals to ionizing radiation in the operating rooms is a serious concern for the safety of personnel and patients. The adverse biological effects of ionizing radiation vary based on the duration of exposure, which generally increases the risk of cancer [5]. Invasive cardiologists are the most exposed to ionizing radiation among health professionals and subsequently lead to an increase in the rate of their somatic DNA damage [6].…”
mentioning
confidence: 99%